Introduction to Cyberbullying Prevention Strategies at SMK Persatuan 2 Tulangan - Arbi, Anggun Purnomo; Jalil , Abdul; Mayasari, Vita (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
This research is an effort to prevent cyberbullying at SMK Persatuan 2 Tulangan. Researchers carried out a series of activities, starting from initial observations, basic education about bullying, cyberbullying prevention seminars, student creative project assignments, to evaluation activities. This effort succeeded in increasing students' understanding of the forms, impacts and strategies to prevent cyberbullying. The program provides a foundation for other schools to adopt similar approaches to help prevent incidents of cyberbullying in educational settings, creating a safer and more positive environment. With cooperation between schools, students, families and communities, this research provides guidance for broader cyberbullying prevention.